2020
DOI: 10.1016/j.jmat.2019.12.011
|View full text |Cite
|
Sign up to set email alerts
|

Variation of contact resonance frequency during domain switching in PFM measurements for ferroelectric materials

Abstract: Piezoresponse Force Spectroscopy (PFS) is a powerful method widely used for measuring the nanoscale ferroelectric responses of the materials. However, it is found that certain non-ferroelectric materials can also generate similar responses from the PFS measurements due to many other factors, hence, it is believed that PFS alone is not sufficient to differentiate the ferroelectric and non-ferroelectric materials. On the other hands, this work shows that there are distinct differences in contact resonance freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 65 publications
(86 reference statements)
1
4
0
1
Order By: Relevance
“…We note that the resonance frequencies at positive voltages in N 4 could be well-described by the non-ferroelectric phenomena, similar to that seen in glass ( Figure S9, Supporting Information) superimposed with a small amount of ferroelectric softening at coercive values. The asymmetric response at negative voltages is tentatively assigned to Schottky barrier [47] formation between tip and sample surface in addition to possible conductive phenomena. [45] The piezoresponse curve can similarly be well-described by a superposition of different conduction-like, non-ferroelectric behaviors.…”
Section: Ti 08 O 3 Thin Films Through Systematic Analysis and Intromentioning
confidence: 90%
“…We note that the resonance frequencies at positive voltages in N 4 could be well-described by the non-ferroelectric phenomena, similar to that seen in glass ( Figure S9, Supporting Information) superimposed with a small amount of ferroelectric softening at coercive values. The asymmetric response at negative voltages is tentatively assigned to Schottky barrier [47] formation between tip and sample surface in addition to possible conductive phenomena. [45] The piezoresponse curve can similarly be well-described by a superposition of different conduction-like, non-ferroelectric behaviors.…”
Section: Ti 08 O 3 Thin Films Through Systematic Analysis and Intromentioning
confidence: 90%
“…In the previous study by Liu et al, 29 it was found that, during the SS-PFM measurements conducted on the ferroelectric materials, f 0 rose to a peak value around the coercive bias where the local effective piezoresponse is zero. In contrast, the non-ferroelectric materials, glass and banana peel, also showed a hysteresis loop in the bias spectroscopic measurements, while the signals of f 0 fluctuated differently.…”
Section: Introductionmentioning
confidence: 84%
“…Note that, for the second and third loadings, two similar peak-shaped fluctuations occur regularly. Referring to the previous study, 29 we consider that these field; (d-f) the score maps for the first three principal components at the off-field; and (g-i) the loadings for the first three principal components at the on-/off-field. The percentages of variance explained by the first, the second, and the third on-field principal components are 83.58%, 4.70%, and 3.87%, respectively; at the off-field, they are 90.80%, 2.88%, and 1.27%, respectively.…”
Section: Electromechanical Responses At the Nanoscalementioning
confidence: 99%
“…The piezoelectric effect is usually measured by piezoresponse force microscopy (PFM), through the estimation of the piezoelectric coefficient d 33 , the obtention of hysteresis loops and switching imaging of the topography showing piezo-active domains [ 17 , 18 ]. However, non-piezoelectric effects [ 10 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ] can induce electromechanical (EM) responses in PFM measurements that resemble the piezoresponse. These can be electrostatic effects [ 25 , 26 , 27 ], electrochemical strain [ 28 , 29 , 30 , 31 ], induced polarization (electrostriction) [ 32 ], flexoelectricity [ 33 , 34 , 35 , 36 ], or thermal expansion due to Joule heating [ 37 ].…”
Section: Introductionmentioning
confidence: 99%